Blood-brain barrier repair: potential and challenges of stem cells and exosomes in stroke treatment - Fu, Xiaochen; Li, Jia; Yang, Shoujun; Jing, Jiapeng; Zheng, Qinzhi; Zhang, Ting; Xu, Zhuo (Frontiers in Cellular Neuroscience, 2025)
Stroke is characterized with high morbidity, mortality and disability all over the world, and one of its core pathologies is blood-brain barrier (BBB) dysfunction. BBB plays a crucial physiological role in protecting brain tissues and maintaining homeostasis in central nervous system (CNS). BBB dysfunction serves as a key factor in the development of cerebral edema, inflammation, and further neurological damage in stroke patients. Currently, stem cells and their derived exosomes have shown remarkable potential in repairing the damaged BBB and improving neurological function after stroke. Stem cells repair the integrity of BBB through anti-inflammatory, antioxidant, angiogenesis and regulation of intercellular signaling mechanisms, while stem cell-derived exosomes, as natural nanocarriers, further enhance the therapeutic effect by carrying active substances such as proteins, RNAs and miRNAs. This review will present the latest research advances in stem cells and their exosomes in stroke treatment, as well as the challenges of cell source, transplantation timing, dosage, and route of administration in clinical application, aiming to discuss their mechanisms of repairing BBB integrity and potential for clinical application, and proposes future research directions. Stem cells and exosomes are expected to provide new strategies for early diagnosis and precise treatment of stroke, and promote breakthroughs in the field of stroke.